A New Approach to Low-Cost, High Performance Chemical Flooding System - Elraies, K.A. (2010)
This paper presents a new Acid-Alkali-Surfactant (AAS) flooding formulation as an alternative to conventional alkaline/surfactant/polymer (ASP) process. It is a cost-effective formula that is able to overcome precipitation problems prevalent with ASP flooding when natural sea water was used. The acid was evaluated in an AAS formulation using sodium carbonate and introducing a new polymeric surfactant derived from Jatropha oil. The feasibility of applying the new AAS formula was demonstrated by a series of experiments involving fluid compatibility test with natural sea water having a large quantity of divalent metal cations, interfacial tension between Angsi crude oil and AAS solution, surfactant adsorption, and core flood using Berea core samples. The acid effectively prevented divalent metal cations from precipitating and all solutions remained clear for 90 days at 90oC. The optimum acid concentration was found to be proportional to alkali concentration in the ratio of 1.66:1. A combination of the new system was found to significantly reduce the IFT and the adsorption level of the surfactant. The best chemical concentrations were then validated in core flood tests using various alkali and surfactant concentrations. The optimum alkali and surfactant concentrations were confirmed as 0.6% and 0.6% respectively. Using the optimum concentrations, another series of core flood tests were conducted by changing the injection volume. Only a small incremental recovery was obtained with slugs higher than 0.5 PV. Injection of 0.5 PV of the formulated slug followed by chase water produced an additional 18.8% OOIP over water flood, accomplishing a total oil recovery of 77.3% OOIP. This makes the new AAS formula an attractive and cost-effective agent for CEOR particularly for offshore field application.